Monologika; Retorika untuk Tabligh Islam (Menelusuri sejarah menemukan arah) - Aang Ridwan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2009)
Retorika has the significant position in oftimalizing tabligh's aim attainment. The top aspect of tabligh that utilizes rhetorics can be recognized on mubaligh’s skill in getting language and managing knowledge that will be passed to audiences so tabligh's message becomes sistematic. In developing history of the monologic's rhetoric has recognized three forms of rhetorics, there are elocusionis , Belles lettris , and teste faculty. (1 ) elocusionis, focusing its study on technic problem of oration forwarding, (2 ) Belletrist, this rhetoric form really accentuates aesthetical lingual and esthetic facet order on writing. (3 ) teste faculty rhetorics, it emphasize teste importance in rhetoric.